Encyclopedia of the mind - Pashler, Harold E. (Thousand Oaks, Calif. : SAGE Publications, Inc., 2013)
It's hard to conceive of a topic of more broad and personal interest than the study of the mind. In addition to its traditional investigation by the disciplines of psychology, psychiatry, and neuroscience, the mind has also been a focus of study in the fields of philosophy, economics, anthropology, linguistics, computer science, molecular biology, education, and literature. In all these approaches, there is an almost universal fascination with how the mind works and how it affects our lives and our behavior. Studies of the mind and brain have crossed many exciting thresholds in recent years, and the study of mind now represents a thoroughly cross-disciplinary effort. Researchers from a wide range of disciplines seek answers to such questions as: What is mind? How does it operate? What is consciousness? This Encyclopedia brings together scholars from the entire range of mind-related academic disciplines from across the arts and humanities, social sciences, life sciences, and computer science and engineering to explore the multidimensional nature of the human mind.
Includes bibliographical references and index.
Keywords: Thought and thinking -- Encyclopedias